KEBERFUNGSIAN SOSIAL DI DAERAH RAWAN KONFLIK - Probosiwi, Ratih (Puslitbangkesos Kementerian Sosial RI, 2018)
This paper aims to determine social functioning in conflict prone areas including status, role, and social norms. Conflict-prone local communities are vulnerable to provocation because of the mistrust between communities that can trigger the clogging of social function in society. The research was conducted in Selok Awar-awar Village, Pasirian Sub-district, Lumajang Regency by seeing the social conflict caused by illegal sand mining which eventually triggered the case of Salim Kancil. Primary data obtained through in-depth interviews, observation, and literature study. Social functionality is discussed in three ways: the ability to meet basic needs, perform social roles, and face shock and pressure. Research shows that communities around the conflict area have difficulty in performing social functions, especially related to the role that is carried out. In general, communities face barriers to meeting basic economic needs due to their lost land and livelihoods; in carrying out its social role, society is limited by intimidation of pro illegal sand mining groups; while in the ability to cope with the pressures of the community are able to manage the conflict without resorting to violence despite intimidation in such a way. It is recommended to assist conflict-prone areas through economic empowerment programs that are capable of implementing two functions, namely as a place for community meetings to reduce disagreements and as a means of increasing revenues to reduce community disparities. Keywords: Conflicts, Social Functioning, Mentoring, Empowerment